#### Answer

$9x\sqrt[3]{xy^2}$

#### Work Step by Step

Factor the radicand of the first radical so that one factor is a perfect cube. Then, simplify to obtain:
$=4\sqrt[3]{x^3(xy^2)}+5x\sqrt[3]{xy^2}
\\=4(x)\sqrt[3]{xy^2} + 5x\sqrt[3]{xy^2}
\\=4x\sqrt[3]{xy^2} + 5x\sqrt[3]{xy^2}$
RECALL:
The distributive property states that for any real numbers a, b, and c:
(1) $ac + bc = (a+b)c$
(2) $ac-bc=(a-b)c$
Use the rule (1) above to combine like terms and obtain:
$=(4x+5x)\sqrt[3]{xy^2}
\\=9x\sqrt[3]{xy^2}$